La responsabilidad subjetiva en el paso a la vida civil - Osorio Doncel, Paula Esperanza (Universidad de San Buenaventura - Cali, 2017)
This article condenses a reflection, which occurred from academics and practitioners in relation to understanding the subject immersed in the phenomena of war interests. Interest that comes from direct approach to people in the process of reintegration. the theoretical reflections of psychoanalysts who favor the research exploring this scenario, in contrast to the discourse of some demobilized interviewed during my practice in one of the five homes Paz willing nationwide to care defected clusters are addressed guerrilla operated by the Program of Humanitarian Attention to the Demobilized the Ministry of National Defense. This article is organized into three sections: the first Introduction to Real dimensions, symbolic and imaginary in the guerrilla organizations, the second: Step into civilian life: a process of Real transit, Symbolic and Imaginary, emphasizing in that the symbolic order that has been built and sustained in the future of the guerrilla organization and prevailing in the legal context and the third: Of the passion for justification to Subjective rectification opinion aims to identify the basis for such rectification this population as a way of approach to the ways of their uniqueness, capped by a uniformity that dilutes their subjectivity as beings of desire in a vast panorama that apparently "forces them" as they relate to rule based on standards Another required by a domineering; In contrast succeed understand that the figure of the guerrilla not been obliged to act based on what is demanded, on the contrary, it has decided to position itself as part of a collective fusion in which no one and which one They are just all.